Study and Proposal of Environmental Improvement and Restoration Plan for Quarry Cluster – A Case Study in Dong Nai Province - Tri Quang Hung, Nguyen; Truong Nhu Thuy, Vo; Minh Ky, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 38 No 2DO - 10.25073/2588-1094/vnuees.4644, 2022)
The quarrying and mining activities can significantly affect the social and natural environment. The study aims to assess the current situation and propose environmental restoration solutions for quarry clusters – a case study in Binh Hoa quarry, Bien Hoa, Dong Nai. In particular, the research studied the persisting environmental and post-mining land use issues and suggested  environmental restoration plans that align with sustainable development of local government. The study used Analytic Hierarchy Process (AHP) to determine the environmental improvement and restoration plans for the post-mining quarry. The results showed the advantages of utilizing the  post-mining land resources, which directly contributed to the local economic development. In addition, the findings can be widely applied to the various mines and quarries in Dong Nai province for sustainable development.